2011
DOI: 10.7201/earn.2009.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Medición de la ecoeficiencia en procesos productivos en el sector agrario. Caso de estudio sobre producción de cítricos

Abstract: The eco-efficiency can be defined by using the “economic value/environmental impacts” ratio. In this study the eco-efficiency of orange production in the Comunidad Valenciana was assessed. 24 scenarios of orange production were built regarding their agricultural practices. For every scenario the environmental impacts were assessed by means of Life Cycle Assessment (LCA) as well as the economic value added. The results have been referred to 1 kg oranges. The integration of the economic and environmental assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 30 publications
3
15
1
6
Order By: Relevance
“…c. Finally, it should be stressed that agri-environmental programs (i.e., the implementation of more environmentally-friendly technologies) seem to improve farms' eco-efficient performance, being an effective policy to reduce environmental pressures stemming from the farming sector. Similar results have been found in other studies, where comparisons between different agricultural systems or production technologies have been achieved (e.g., Basset-Mens et al, 2007;Pelletier et al, 2008;or Ribal et al, 2009). However, it is worth pointing out that the payments received by farmers subscribing agri-environmental contracts are theoretically equivalent, according to CAP regulations, to the additional costs needed to fulfil program requirements that go beyond the conditionality of the CAP single payment requested from all producers.…”
Section: Explaining Eco-efficiencysupporting
confidence: 70%
See 2 more Smart Citations
“…c. Finally, it should be stressed that agri-environmental programs (i.e., the implementation of more environmentally-friendly technologies) seem to improve farms' eco-efficient performance, being an effective policy to reduce environmental pressures stemming from the farming sector. Similar results have been found in other studies, where comparisons between different agricultural systems or production technologies have been achieved (e.g., Basset-Mens et al, 2007;Pelletier et al, 2008;or Ribal et al, 2009). However, it is worth pointing out that the payments received by farmers subscribing agri-environmental contracts are theoretically equivalent, according to CAP regulations, to the additional costs needed to fulfil program requirements that go beyond the conditionality of the CAP single payment requested from all producers.…”
Section: Explaining Eco-efficiencysupporting
confidence: 70%
“…13 It is worth pointing out that, as far as we know, there is no closely related work in the literature where the determinants of eco-efficiency at farm level have being analysed, as we do in this paper. Thus, our discussion of the results is based on other related studies, including those comparing the eco-efficiency of different agricultural systems or production technologies (e.g., Basset-Mens et al, 2007;Pelletier et al, 2008or Ribal et al, 2009) and those employing other methodologies but with a similar purpose (e.g., studies based on sustainable efficiency as Van Passel et al, 2007;Meul et al, 2007or Van Passel et al, 2009, or relying on sustainability assessment through composite indicators, such as Gómez-Limón and Sanchez-Fernandez, 2010).…”
Section: Explaining Eco-efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…For citrus orchards, our study found similar specific GHG emissions to those reported in Italy for orange (0.10 kg CO 2eq kg À1 ) [39], and lower than that estimated in Sicily for orange (0.13 kg CO 2eq kg À1 ) and lemon productions (0.12 kg CO 2eq kg À1 ) [40]. Our data were also significantly lower than those estimated in Valencia for orange (0.25 kg CO 2eq kg À1 ) [41].…”
Section: Per Crop Characterisation Of Ghg Emissionssupporting
confidence: 61%
“…Data Envelopment Analysis (DEA) has been successfully used for this purpose (Ribal et al, 2009;Sanjuán et al, 2011;Jan et al, 2012). In this way, the eco-efficiency of the farms is measured and benchmark values can be defined.…”
Section: Discussionmentioning
confidence: 99%